Assessing symmetric price transmission by using threshold cointegration in Iranian egg market. Issue 6 (28th August 2019) - Aghabeygi, Mona; Antonioli, Federico; Arfini, Filippo
Abstract : Purpose: Eggs bear an essential role in Iranian diet, primarily for their protein content. The egg production strictly depends on the price of inputs, that is corn used for poultry feeding. The upsurge in corn prices in recent years gave rise to both consumers' and producers' dissatisfaction, increasing production cost and the egg price in the final market. The purpose of this paper is to investigate the price-transmission dynamics between corn and retail egg prices in Iran. Design/methodology/approach: Individual commodity price series generally contain stochastic trends and they are non-stationary. Standard unit root and cointegration tests will be conducted in order to determine whether price series are stationary and whether they are cointegrated, respectively. The existence of cointegration between the two-price series depends on the nature of autoregressive process. If there is an asymmetric convergence between two variables, then Engle and Granger's (1987) test can have a misspecification error and the result cannot indicate nature of variables. Threshold or asymmetric convergence test should be used, which can detect the asymmetric behavior of variables and threshold effects on series. Findings: Results showed that, in the long run, owing to price transmission, any price shocks on corn price will be transmitted to the egg price. Practical implications: Policy makers should implement input and output price policies to support producer and consumer in the retail market to increase consumer and producer welfare, and they should also control intermediaries in this market. Originality/value: This research dealing with price transmission has been concerned only with applying time-series modeling techniques to price data. The main focus of this approach has been to characterize vertical price relationships by the extent, speed and nature of the adjustments through the supply chain to market shocks generated at different levels in the marketing process. Thus, it complements the marketing margin models, which are mainly concerned with testing for market imperfections and calculating the price transmission. Besides these points, particular importance has been given in this research to the question of symmetry of price adjustments.